From A to Z: Effects of a 2nd-grade reading intervention program for struggling readers - Jo\~ao Lopes; Pedro S. Martins; Célia Oliveira; Jo\~ao Ferreira; Jo\~ao Tiago Oliveira; Nuno Crato (Global Labor Organization (GLO), 2024)
Many children in primary grades show difficulties with reading fluency, hardly reading text or doing it effortfully and fruitlessly, making intervention programs for struggling readers a priority for researchers and schools. This paper analyzes the results of a reading intervention program for 182 second grade struggling readers from public schools. Students received a multi-component program, including repeated readings, word recognition, morphological analysis, text interpretation, and writing skills. Participants received about fifty 45-minute intervention sessions over the school year. Using a difference-in-differences, quasi-experimental within-group longitudinal design (three-point measurements), we found that the intervention group progressed significantly faster than a classmate control group in all reading outcomes (speed, accuracy, and expressiveness). By the end of the school year, differences between the intervention and control groups in accuracy and expressiveness become small but are still large in reading speed.
Keywords: I21; I26; 330; struggling readers; intervention program; reading speed; accuracy; expressiveness; difference-in-differences